Redescription of the Hispaniolan ladybird genus Bura Mulsant (Coleoptera: Coccinellidae) and justification for its transfer from Coccidulinae to Sticholotidinae - Vandenberg, Natalia J.; Perez-Gelabert, Daniel E. (Zootaxa, 2007)
The Hispaniolan genus Bura Mulsant is removed from Coccidulinae and placed in Sticholotidinae. The characteristics which justify this transfer are discussed and an historical review of the classification of the Sticholotidinae is presented. Bura is diagnosed and redescribed, and its affinities to other Sticholotidini are discussed. Illustrations of key generic characters are provided.